2020
DOI: 10.1088/2058-6272/ab770c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of turbulence rotation in the SOL and plasma edge of W7-X for different magnetic configurations

Abstract: The W7-X stellarator is optimized for neoclassical transport and turbulent transport plays an important role. It is equipped with a inertial cooled Graphite divertor which intersects, depending on the magnetic configuration the island chain at the plasma edge. Additional control coils and the plasma current modify the iota profile at the plasma edge and shift the position of the island chain. To monitor the effects on the poloidal propagation velocity in the scrape off layer (SOL) and the plasma edge an O-mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Second, if a strong E r shear is present, the resulting shear flow may decorrelate turbulent structures, thereby reducing turbulence [30]. Turbulence suppression by E r shear has been observed in W7-X [31,32] and the stabilization effect of E r has been studied by means of gyrokinetic simulations, which confirmed the existence of this mechanism but found its effect to be less than that of profiles [16,33]. Finally, ITG modes are not the only possible instabilities in the k ⊥ ρ i 1 scale.…”
Section: Introductionmentioning
confidence: 99%
“…Second, if a strong E r shear is present, the resulting shear flow may decorrelate turbulent structures, thereby reducing turbulence [30]. Turbulence suppression by E r shear has been observed in W7-X [31,32] and the stabilization effect of E r has been studied by means of gyrokinetic simulations, which confirmed the existence of this mechanism but found its effect to be less than that of profiles [16,33]. Finally, ITG modes are not the only possible instabilities in the k ⊥ ρ i 1 scale.…”
Section: Introductionmentioning
confidence: 99%
“…The divertor control coils with two coils per module, are available to adjust the divertor islands in position and shape. Applying positive currents in both coils increases the size of the island and negative currents will decrease its size [34,35]. In addition, the inverted currents are capable of sweeping the island position, poloidally.…”
Section: Experimental Set Up On W7-xmentioning
confidence: 99%
“…In the Alcator C-Mod tokamak, Shikama et al observed that significant poloidal asymmetry can exist in the impurity density, ion temperature and main ion density in the edge pedestal region [9,10]. In TEXTOR [11] and Tore Supra [12], higher poloidal velocities of the density fluctuations on the outboard side have been observed and the asymmetry present in the Tore Supra tokamak is explained by considering the balloon type structure of the convective cells in the underlying turbulence. However, experimental measurements of neutral temperature on poloidal asymmetries are quite sparse.…”
Section: Nuclear Fusionmentioning
confidence: 99%